Fighting “zombie” health apps through K-Factor virality and other mobile gaming techniques – The application of commercial gaming techniques to create more effective mHealth solutions - Sorcha Moore (Frontiers in Public Health, 2015)
Background Mobile today is recognised as being one of the highest value channels in the marketing mix . The potential for mobile applications to influence user behaviour and establish behavioural habits at scale is evidenced in apps such as Cow Clicker and Candy Crush attracting massive active audiences at their peak, and high levels of viral growth and user activity. mHealth has enormous potential to effect positive behavioural change for health. However with an estimated 80% of overall apps in the app stored being reported as “Zombie” apps , and a reported 80% of health apps being removed after just one use it is evident that sustained impact via mobile health app solutions is difficult to achieve. During the development of the Knowsley Health Hub, a mobile app designed to instigate healthy lifestyle changes in communities, we looked at what can we learn from the success of mobile games to enable us to best utilize the mobile channel as a tool to deliver on this goal. This presentation shows how we examined commercial gaming techniques to create a framework for the delivery of a healthy behaviour intervention programme via the mobile medium and devise a method of evaluation of success.